Legal Implementation of Children as Perpetrators of Sexual Violence - Ilman, Nur Hayanti; Alhadi, Muhammad Nurcholis (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2025)
The implementation of the law on children involved in sexual violence criminal offenses is discussed in the verdict of case Number: 5/Pid.Sus-Anak/2024/PN.Smr. This action is classified as a criminal act of sexual violence falling under the category of immoral acts. Cases involving children are increasing, including sexual violence committed by children themselves. Article 81 of the Indonesian Criminal Code provides a general explanation regarding sexual offenses against children, including acts of violence or threats carried out through deception, lies, or persuasion to engage in sexual acts. Based on the facts found, the actions committed by the defendant involved in sexual violence against the victim occurred more than once. This study aims to examine the applicable legal provisions for children involved with the law and the considerations of judges in handling cases of children committing sexual violence. The research method applied is a normative legal approach.